Limits of the freedom to perform the research profession and significance of research ethics and researcher’s deontology. A case study of respect for intellectual property rights when publishing research results – part I - Chorążewska, Anna; Dajka, Jerzy (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
The term ‘profession in which the public repose confidence’ is a constitutional term in Poland. The Constitution provides that the legislator may create professions of public trust. Self-government of a public trust profession, within the limits of that interest and for its protection, is entitled to represent the interests of persons exercising such professions and, moreover, to supervise the proper exercise of the profession. This paper demonstrates that the profession of a scientist fulfils the prerequisites of a profession of public trust. Scientists performing professional research activities in the institutions within the system of higher education and science form an international scientific community. At various jurisdictional levels, this community has been universally mandated to define the principles of ethics in science and the deontology of the research profession. The task of overseeing proper conduct of research by scientists as persons of public trust is, in turn, entrusted to the ethical and disciplinary committees established in the system of science. In this paper, we examine the rules in force in the scientific community for respecting intellectual property rights when publishing research results and then, in a survey, clarify whether these rules are known to and applied in the international academic community.